EHEALTH EFFICACY IN GHANAIAN NURSING: A PILOT THEMATIC ANALYSIS ON BENEFITS AND CHALLENGES - Jacob Owusu Sarfo; Michael Asiedu (European Scientific Journal, ESJ, 2013)
Nursing informatics serves global health care with information processing and communication functions like staff development and quality patient care services. The incorporation of computers into nursing in many developing countries though essential, has been on a decline growth. This qualitative study examined personnel and organizational factors that affect nursing informatics. A qualitative descriptive study design was employed. Respondents were registered nurses selected from the various health system levels. A total of 18 in-depth interviews were done. Interview data were analysed by using a thematic approach of qualitative analysis.Both senior and junior nursing staff had a fair knowledge of computers and some basic Microsoft applications. They both appreciated the need for immense incorporation of computers into Ghanaian nursing care although lacked organizational support. Rank, gender and age of respondents played immense role in their perception of importance computer skill acquisition and usage while lack of programmed nursing software worsened the case.These findings suggest that measures focused on incorporating computers to aid nursing care in practice must look at the personnel and organizational issues critically to attain immense achievement.